PATHOMORPHOLOGY OF ADRENAL GLAND TUMORS AND HYPERPLASIAS (International journal of medical sciences, 2025)
Adrenal gland tumors and hyperplasias represent a diverse group of lesions with distinct morphological, functional, and clinical characteristics. Their pathomorphology ranges from benign cortical adenomas to highly aggressive adrenocortical carcinomas, as well as medullary neoplasms such as pheochromocytoma. Hyperplastic conditions, both nodular and diffuse, constitute an important category associated with endocrine disorders including Cushing’s syndrome, primary aldosteronism, and congenital adrenal hyperplasia. This study provides a comprehensive description of the structural and microscopic features of adrenal cortical and medullary tumors and hyperplasias, emphasizing their diagnostic criteria and clinicopathological significance.